PC.110 Hypothermia for Encephalopathy in Low and Middle-Income Countries (HELIX): A Feasibility Study. (9th June 2014) - Pauliah, SS; Narayanan, E; Kumutha, K; Vijaykumar, M; Nair, M; Shankaran, S; Thayyil, S
Abstract : Background: Therapeutic hypothermia improves outcomes after neonatal encephalopathy in high-income countries, however the safety and efficacy of cooling in low- and middle-income countries (LMIC) is not known. Objective: To examine the feasibility of whole body cooling using an inexpensive servo-controlled cooling device developed for use in LMIC. Design: We recruited 28 newborns (>36 wk and >1.8 kg) aged <6 h, admitted to the neonatal unit at Madras Medical College, India, with moderate or severe neonatal encephalopathy. After informed parental consent, infants were kept naked on a cooling mattress attached to the device (Tecotherm-HELIX), circulating water mixed with alcohol. Following 72 h of cooling, infants were passively rewarmed by switching off the machine and covering the infant with warm clothes. Results: 4/16(25%) infants with moderate encephalopathy, and 8/12(67%) with severe encephalopathy died. Thrombocytopenia was seen in 19(68%) infants, gastric bleeds in 10(36%), persistent acidosis in 1(4%) and sclerema in 1(4%). Mean (SD) age and temperature at start of cooling was 4.1(1.1) h, and 35.7(1.5) ° C respectively. Mean (SD) induction time was 79(47) minutes, core temperature during cooling was 33.5(0.1) ° C, and passive re-warming rate was 0.3(0.1) ° C/h (Figure ). The ambient temperature of the intensive care unit was 26–33 ° C. No additional nursing input was required to maintain cooling except refilling the machine with water every 6–8h. The cooling mattress had to be replaced once during the six month study period. Conclusions: Effective therapeutic hypothermia can be provided using Tecotherm-HELIX with minimal additional nursing input in LMIC. Future clinical trials should examine the safety and efficacy of cooling in these settings.